Hypolipidemic Activity of Sesquiterpene Lactones and their Derivatives - Adekenov, Sergazy; Mareška, Václav; Ivanov, Vladimir; Maslova, O. V.; Doskaliyev, Aidos; Shaidarov, M. Z.; Spiwok, Vojtech (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Despite the available range of lipid-lowering drugs, mainly of synthetic origin, the problem of atherosclerosis therapy and its manifestations remain unresolved. Bioinformatics methods, in particular molecular docking, are considered as a promising direction in terms of developing effective original lipid-lowering drugs. Today, as a promising source of natural lipid-lowering agents, it is advisable to consider natural terpenoids, namely sesquiterpene lactones, which are distinguished by a wide range of pharmacological activity. This article presents the results of a virtual and biological screening of the lipid-lowering activity of sesquiterpene γ-lactones and their chemically modified derivatives. AIM: The aim is to evaluate the lipid-lowering properties of samples of sesquiterpene γ-lactones and their derivatives by virtual and biological screening methods. METHODS: Molecular modeling of the binding energy of the “ligand-target” complex (docking). Molecular docking of the lipid-lowering activity of sesquiterpene γ-lactones and their derivatives was performed using the Glide program from the developer of the Schrodinger Small-Molecule Drug Discovery package using the Extra Precision algorithm (https://www.schrodinger.com/glide). The effect of sesquiterpene lactones on the expression of genes for key enzymes of lipid metabolism in the liver was studied in an in vivo model of hyperlipidemia caused by an atherogenic diet. CONCLUSION: Virtual screening of the lipid-lowering activity of sesquiterpene γ-lactones and their derivatives by molecular docking revealed a number of promising compounds (matricin, matricarin, grossmisin oxime, austricin oxime, 5β (H)-austricin) receptor interactions on the enzyme system cholesterol 7α-hydroxylase (CYP7A1). New mechanisms of lipid-lowering activity for sesquiterpene γ-lactones were proposed, which were established in the study of gene expression of key enzymes of lipid metabolism in the liver in a model of hyperlipidemia caused by an atherogenic diet in rats under in vivo conditions.